2022
DOI: 10.1155/2022/8652741
|View full text |Cite
|
Sign up to set email alerts
|

Dl-3-n-Butylphthalide Improves Neuroinflammation in Mice with Repeated Cerebral Ischemia-Reperfusion Injury through the Nrf2-Mediated Antioxidant Response and TLR4/MyD88/NF-κB Signaling Pathway

Abstract: Increasing evidence shows that oxidative stress and neuroinflammation play a crucial role in the pathology of vascular dementia (VD). Previously, we have found that Dl-3-n-butylphthalide (NBP) has antioxidant and anti-inflammatory activities in VD, whereas little is known about its mechanism. Therefore, the objective of our study was to explore the contribution of nuclear factor erythroid-2 related factor 2 (Nrf2) to NBP and its effects on anti-inflammatory activity in a mouse model of VD. Our studies revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Numerous studies have shown that nerve inflammation mediated by TLR4 activation plays a key role in stroke, AD, and other neurological diseases at the onset of systemic disease. Due to the complex mechanism involved in the pathogenesis, the treatment is controversial, leading to different roles in the study of the neurological inflammatory disease (12)(13)(14). Therefore, we established a VD rat model through 4 vessel occlusion (4-VO) operation.…”
Section: Original Articlementioning
confidence: 99%
“…Numerous studies have shown that nerve inflammation mediated by TLR4 activation plays a key role in stroke, AD, and other neurological diseases at the onset of systemic disease. Due to the complex mechanism involved in the pathogenesis, the treatment is controversial, leading to different roles in the study of the neurological inflammatory disease (12)(13)(14). Therefore, we established a VD rat model through 4 vessel occlusion (4-VO) operation.…”
Section: Original Articlementioning
confidence: 99%
“…Another study showed that the protective effect of Dl-3-n-butylphthalide (NBP) on neuroinflammation in mice with CIRI was related to Nrf2. Nrf2 regulates the TLR4/MyD88/NF-κB pathway to participate in this neuroprotective effect [ 140 ].…”
Section: Activation Of Nrf2 Signaling Pathway In Cerebral Ischemic St...mentioning
confidence: 99%
“…The regulation of NF-κB activity by Nrf2 is manifested in inhibiting inflammatory responses. Studies have shown that Nrf2 can regulate the TLR4/MyD88/NF-κB pathway in CIRI models and play a neuroprotective role [ 140 ]. Another target gene of Nrf2, p62, can regulate antioxidant and inflammatory activities.…”
Section: The Role and Mechanism Of Nrf2 In Cerebral Ischemic Strokementioning
confidence: 99%
“…* sı Supporting Information ABSTRACT: Five new xenicane diterpenes, including three rare nitrogen-containing derivatives, dictyolactams A (1) and B (2) and 9-demethoxy-9-ethoxyjoalin (3), a rare diterpene with a cyclobutanone moiety, named 4-hydroxyisoacetylcoriacenone (4), and 19-O-acetyldictyodiol (5), were isolated from an East China Sea collection of the brown alga Dictyota coriacea, along with 15 known analogues (6−20). The structures of the new diterpenes were elucidated by spectroscopic analyses and theoretical ECD calculations.…”
mentioning
confidence: 99%
“… 1 Nrf2/ARE signaling pathway is the most important endogenous defense system protecting nerve cells against oxidative damage. 2 Some natural products derived from terrestrial plants, such as britanin, 3 swertiamain, 4 and dl-3- n -butylphthalide, 5 have proven to be able to prevent and mitigate CIRI by activating Nrf2 and enhancing antioxidant gene expression in the preclinical studies. However, the potential of marine natural products as novel neuroprotective antioxidants against CIRI has been rarely studied yet.…”
mentioning
confidence: 99%